2020
DOI: 10.1101/2020.06.10.20127209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic accuracy study of a novel blood-based assay# for identification of TB in people living with HIV

Abstract: A non-sputum triage test to rule out TB disease is a WHO high-priority diagnostic and a combinatory score based on a 3-gene host-signature has shown promise in discriminating TB from other illnesses. We evaluated the accuracy of an early-prototype cartridge-assay (Xpert MTB Host Response, or Xpert-MTB-HR-Prototype) of this 3-gene signature on bio-banked blood-samples from PLHIV against a comprehensive microbiological reference standard (CMRS) and against Xpert MTB/RIF on first sputum alone. We depict results b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
4
8
0
Order By: Relevance
“…Our results corroborate a previous study conducted by Södersten and colleagues in a very different population and clinical setting-screening HIVinfected individuals presenting with TB symptoms to clinics in South Africa and Peru-which demonstrated feasibility of measuring the 3-gene signature on this platform. 11 Consistent with this and earlier studies on the 3-gene signature, we found that TB cases had lower Xpert-MTB-HR scores, indicating higher expression levels (up-regulation) of GBP5 and DUSP3 compared with KLF2, compared with controls. [9][10][11]20 The AUC in this study (0.84) was lower than that reported by Södersten (0.94 against sputum Xpert MTB/RIF), 11 but consistent with a previous smaller evaluation of the 3-gene signature by laboratory-based qRT-PCR in this low HIVprevalence, actively screened population (0.87).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results corroborate a previous study conducted by Södersten and colleagues in a very different population and clinical setting-screening HIVinfected individuals presenting with TB symptoms to clinics in South Africa and Peru-which demonstrated feasibility of measuring the 3-gene signature on this platform. 11 Consistent with this and earlier studies on the 3-gene signature, we found that TB cases had lower Xpert-MTB-HR scores, indicating higher expression levels (up-regulation) of GBP5 and DUSP3 compared with KLF2, compared with controls. [9][10][11]20 The AUC in this study (0.84) was lower than that reported by Södersten (0.94 against sputum Xpert MTB/RIF), 11 but consistent with a previous smaller evaluation of the 3-gene signature by laboratory-based qRT-PCR in this low HIVprevalence, actively screened population (0.87).…”
Section: Discussionsupporting
confidence: 92%
“…11 Consistent with this and earlier studies on the 3-gene signature, we found that TB cases had lower Xpert-MTB-HR scores, indicating higher expression levels (up-regulation) of GBP5 and DUSP3 compared with KLF2, compared with controls. [9][10][11]20 The AUC in this study (0.84) was lower than that reported by Södersten (0.94 against sputum Xpert MTB/RIF), 11 but consistent with a previous smaller evaluation of the 3-gene signature by laboratory-based qRT-PCR in this low HIVprevalence, actively screened population (0.87). 10 Earlier studies have also investigated CRP testing for distinguishing individuals with active TB from those without disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, such a conserved gene signature, identified using a large amount of heterogeneous data across multiple cohorts, can be further analyzed to identify a parsimonious, clinically useful, point-of-care test that is generalizable across patient populations. For example, we have previously described a 3-gene host response-based signature for diagnosis of tuberculosis that has been shown to be generalizable across a large number of patient populations, and has been translated into a proof-of-concept point-of-care cartridge with high accuracy (Sodersten et al, 2020). In addition, given the high pairwise correlation between genes within each module, only a small subset of genes within each module would provide the same discriminatory power, further allowing the selection of a parsimonious gene signature.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 3-gene host response-based signature has been repeatedly demonstrated to predict progression from latent Mycobacterium tuberculosis (Mtb) infection to active tuberculosis 6 months prior (Gupta et al, 2020; Turner et al, 2020; Warsinske et al, 2018). Finally, and most importantly, these generalizable robust host response-based signatures can be translated onto a targeted platform as a point-of-care test with rapid turnaround time (Sodersten et al, 2020).…”
Section: Introductionmentioning
confidence: 99%